2019
DOI: 10.1037/pst0000225
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between trainee therapist traits with the use of self-disclosure and immediacy in psychotherapy.

Abstract: The goal of the present study was to explore how self-disclosure (SD) and immediacy relate to trainee therapists' personal characteristics. A prospective multitrait multimethod assessment approach was utilized to assess a wide range of trainee characteristics at the beginning of graduate school. Results showed a significant, positive relationship between trainee interpersonal problems and SD for trainees (n ϭ 33) in their third psychotherapy session with their first patient. Moreover, greater use of SD correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…For instance, trainees with an anxious attachment may fear criticism or rejection if they use immediacy, whereas avoidant trainees may undervalue and avoid such direct communication, patterns consistent with adult attachment theory (Mikulincer & Shaver, 2016). Relatedly, Jowers et al (2019) found that therapist arousal was heightened after sessions with immediacy, and Berg et al (2016) found that therapists felt confused and struggled to stay attuned to emotions when using immediacy. As well, Joo et al (2019) found that Korean therapists were concerned that clients may be resistant, avoidant, or not return if immediacy were used, especially early in therapy.…”
Section: Theory and Empirical Research About Immediacymentioning
confidence: 99%
“…For instance, trainees with an anxious attachment may fear criticism or rejection if they use immediacy, whereas avoidant trainees may undervalue and avoid such direct communication, patterns consistent with adult attachment theory (Mikulincer & Shaver, 2016). Relatedly, Jowers et al (2019) found that therapist arousal was heightened after sessions with immediacy, and Berg et al (2016) found that therapists felt confused and struggled to stay attuned to emotions when using immediacy. As well, Joo et al (2019) found that Korean therapists were concerned that clients may be resistant, avoidant, or not return if immediacy were used, especially early in therapy.…”
Section: Theory and Empirical Research About Immediacymentioning
confidence: 99%